Genomic and metabolomic insights into the antimicrobial compounds and plant growth-promoting potential of Bacillus velezensis B115 - Jili Chen; Yuzhou Feng; Junchi Ma; Qing Zhang; Yumei Dong; Dongjie Li; Xuemei Duan; Lequn Zhou; Zhihua Li; Ying Yang; Bo Cai; Ze Liu; et al. (Scientific Reports)
Abstract The B115 strain, isolated from the inter-root soil of healthy plants in a continuous cropping site of Panax notoginseng, was identified as Bacillus velezensis B115 by 16S rDNA sequence comparison and comparative genomic analysis. B115 is a strain of beneficial microorganisms present in the inter-root zone of plants, with favorable plant growth-promoting properties and antagonistic effects against the plant pathogen Fusarium oxysporum. However, the whole genome of B115 remains unclear, thus restricting its potential applications. To address this gap, the whole genome of B115 has been sequenced and annotated to elucidate the molecular mechanisms underlying its plant growth-promoting and antimicrobial activities. The genome analysis revealed that B115 comprises a single circular chromosome of 4,200,774 bp and a plasmid region 16,878 bp long, possessing a GC content of 45.95%. Moreover, 4349 protein-coding genes were predicted. Notably, the B115 genome contains a substantial number of genes (103) involved in the biosynthesis, transport, and catabolism of secondary metabolites. Through genome mining, 13 BGCs and 540 genes encoding secondary metabolites with predicted roles were identified, including members of the surfactin and fengycin families. Utilizing LC–MS/MS technologies, 2318 metabolites were detected in the fermentation broth of B. velezensis B115, encompassing compounds such as Corynebactin, Gamabufotalin, Pracinostat, Indoleacetic acid, (8)-Gingerol, Luteolin, Liquiritigenin, and other metabolites with antimicrobial, growth-promoting, antioxidant, and antitumor properties. By exploring secondary metabolite-related genes and predicting potential secondary metabolites from the B115 genome based on the whole-genome sequence results, we further elucidate the genomic basis for its ability to promote plant growth and inhibit pathogen activity.